2021
DOI: 10.1021/acs.jafc.1c02535
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of γ-Glutamylvalylglycine Using Bacterial γ-Glutamyltranspeptidase

Abstract: γ-Glutamylvalylglycine is known as a potent "kokumi" substance that increases the thickness, continuity, and mouthfulness of the taste of food. In this study, γ-glutamylvalylglycine was enzymatically synthesized from glutamine and valylglycine through the transpeptidation reaction of bacterial γ-glutamyltranspeptidase. The reaction conditions decided for the production of γglutamylvalylglycine are 20 mM glutamine, 100 mM valylglycine, 30 mU/mL γ-glutamyltranspeptidase, and 0.856 M (5%) NaCl at pH 8 and 37 °C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…However, no significant differences ( P > 0.05) were observed between the percentage of maximum GGT activity at pH 9.0 measured using Tris–HCl buffer and NH 4 OH-NH 4 Cl buffer. It has been reported that there was no significant difference in the concentration of γ-Glu-Val-Gly synthesized with Tris–HCl buffer and NH 4 OH-NH 4 Cl buffer, which was in line with our results. Nevertheless, using the same assay for the measurement of GGT activity, Baumrucker proposed that the GGT activity of skim milk membranes and milk fat globule membranes was the highest at pH 8.0, and the difference of optimum pH value might be thus attributed to the bovine breeds.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, no significant differences ( P > 0.05) were observed between the percentage of maximum GGT activity at pH 9.0 measured using Tris–HCl buffer and NH 4 OH-NH 4 Cl buffer. It has been reported that there was no significant difference in the concentration of γ-Glu-Val-Gly synthesized with Tris–HCl buffer and NH 4 OH-NH 4 Cl buffer, which was in line with our results. Nevertheless, using the same assay for the measurement of GGT activity, Baumrucker proposed that the GGT activity of skim milk membranes and milk fat globule membranes was the highest at pH 8.0, and the difference of optimum pH value might be thus attributed to the bovine breeds.…”
Section: Resultssupporting
confidence: 93%
“…As for the glutamine concentration in γ-glutamylated hydrolysates, it was significantly lower than that in the original hydrolysates ( P < 0.05). Moreover, the glutamine content of γ-glutamylated hydrolysates treated by bovine milk GGT was significantly higher than that of its counterpart generated by bacterial GGT, especially after the addition of glutamine, suggesting that more glutamine was incorporated into the generation of γ-glutamyl peptides catalyzed by bacterial GGT. , …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Increasing the substrate, such as the acceptor concentration, is not possible due to solubility limitations. The optimal donor:acceptor ratio (1:5) was maintained by feeding Gln every 5 h up to 20 h into the reactor, which led to 1.7 times better yield relative to the yield without periodic Gln feeding (Table 2) [33].…”
Section: Optimization Involving Multiple Enzymesmentioning
confidence: 99%
“…The strain was grown and GGT was purified using Nickel Sepharose 6 Fast Flow resin (GE Healthcare; Chicago, IL) as described previously. 29 Measurement of GGT Activity. Enzyme activity was measured as described previously.…”
Section: ■ Introductionmentioning
confidence: 99%